Erosion Hazard Levels in Padang Batung Sub-district, Hulu Sungai Selatan Regency, South Kalimantan Province, Indonesia - Adriyan Renaldi; Deasy Arisanty; Muhammad Muhaimin; Akhmad Munaya Rahman; Aswin Nur Saputra (MO.RI Publishing, 2023)
Erosion is a form of damage to the soil caused by changes in land function on certain plains without management. The Padang Batung Sub-district area experienced land damage which was characterized by the distribution of critical land area reaching half of the area. The purpose of this study is to analyze the level of erosion hazards that occur in Padang Batung Sub-district. This study used a terrain unit map as the basis for the sample analysis unit. The number of samples in this study was 20 samples using the purposive random sampling method. The data analysis used is in the form of the Universal Soil Loss Equation (USLE) equation which can predict the level of erosion hazard through several parameters in the study area. The results showed that the erosion hazard level in Padang Batung Sub-district was dominated by severe criteria with an affected area of 74 km2 with an average erosion rate of 345.27 tons/ha/yr. One of the dominating factors causing the high erosion in Padang Batung Sub-district to be included in the medium and high classification is rain intensity, high erodibility, unstable topography and land cover vegetation.